CaMKII and stress mix it up in mitochondria - Joiner, Mei-ling A.; Koval, Olha M. (Frontiers in Pharmacology, 2014)
CaMKII is a newly discovered resident of mitochondria in the heart. Mitochondrial CaMKII promotes poor outcomes after heart injury from a number of pathological conditions, including myocardial infarction (MI), ischemia reperfusion (IR), and stress from catecholamine stimulation. A study using the inhibitor of CaMKII, CaMKIIN, with expression delimited to myocardial mitochondria, indicates that an underlying cause of heart disease results from the opening of the mitochondrial permeability transition pore (mPTP). Evidence from electrophysiological and other experiments show that CaMKII inhibition likely suppresses mPTP opening by reducing Ca2+ entry into mitochondria. However, we expect other proteins involved in Ca2+ signaling in the mitochondria are affected with CaMKII inhibition. Several outstanding questions remain for CaMKII signaling in heart mitochondria. Most importantly, how does CaMKII, without the recognized N-terminal mitochondrial targeting sequence transfer to mitochondria?